Soilless biofortification, bioaccessibility, and bioavailability: Signposts on the path to personalized nutrition - Renna, Massimiliano; D’Imperio, Massimiliano; Maggi, Stefania; Serio, Francesco (Frontiers in Nutrition, 2022)
Propelled by an ever-growing awareness about the importance of following dietary recommendations meeting specific biological requirements linked to a person health status, interest in personalized nutrition is on the rise. Soilless biofortification of vegetables has opened the door to the potential for adapting vegetable production to specific dietary requirements. The evolution of vegetables biofortification toward tailored food is examined focusing on some specific categories of people in a context of personalized nutrition instead to simple describe developments in vegetables biofortification with reference to the single element or compound not adequately present in the daily diet. The concepts of bioavailability and bioaccessibility as a useful support tool for the precision biofortification were detailed. Key prospects for challenges ahead aiming to combine product quality and sustainable are also highlighted. Hydroponically cultivation of vegetables with low potassium content may be effective to obtain tailored leafy and fruit vegetable products for people with impaired kidney function. Simultaneous biofortification of calcium, silicon, and boron in the same vegetable to obtain vegetable products useful for bone health deserve further attention. The right dosage of the lithium in the nutrient solution appears essential to obtain tailored vegetables able to positively influence mental health in groups of people susceptible to mental illness. Modulate nitrogen fertilization may reduce or enhance nitrate in vegetables to obtain tailored products, respectively, for children and athletes. Future research are needed to produce nickel-free vegetable products for individuals sensitized to nickel. The multidisciplinary approach toward tailored foods is a winning one and must increasingly include a synergy between agronomic, biological, and medical skills.